2001
DOI: 10.1007/s001980170153
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Bone Mineral Density in Ambulatory Women Living in Buenos Aires, Argentina

Abstract: The aim of this study was to determine possible associations between bone mineral density (BMD), 25-hydroxyvitamin D (25(OH)D) and intact parathyroid hormone (PTH). In a retrospective study we examined the case notes of free-living postmenopausal women living in our city (34 degrees S). We also report a low prevalence of vitamin D deficiency (25(OH)D < 25 nmol/1, 5.6%) and of secondary hyperparathyroidism (intact PTH > 65 pg/ml, 7.5%). Age was correlated with BMD at the lumbar spine (r = -0.25, p = 0.00038) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…This study showed a cut-off level of 25(OH)D of 68 nmol/L at which serum PTH began to increase [78]. Another study in ambulatory women from Buenos Aires showed differences in 25(OH)D levels in summer (63 nmol/L) and winter (53 nmol/L) [79]. Neonates and mothers from the southernmost province had lower 25(OH)D than those from Buenos Aires [80], and a proposal for a supplementation scheme for children in that province (twice single doses of 100,000 IU ergocalciferol every 3 months during autumn and winter) resulted in a safe recovery of 25(OH) D levels [81].…”
Section: Latin Americamentioning
confidence: 58%
See 1 more Smart Citation
“…This study showed a cut-off level of 25(OH)D of 68 nmol/L at which serum PTH began to increase [78]. Another study in ambulatory women from Buenos Aires showed differences in 25(OH)D levels in summer (63 nmol/L) and winter (53 nmol/L) [79]. Neonates and mothers from the southernmost province had lower 25(OH)D than those from Buenos Aires [80], and a proposal for a supplementation scheme for children in that province (twice single doses of 100,000 IU ergocalciferol every 3 months during autumn and winter) resulted in a safe recovery of 25(OH) D levels [81].…”
Section: Latin Americamentioning
confidence: 58%
“…Therefore, both latitude and seasons influence the degree of possible solar radiation a population may receive. The literature reports strong evidence that hypovitaminosis D is greater in winter months for all age groups in Asia [25,26], Europe [69,72,82], Latin America [79], Middle East [91], North America [153], and Oceania [142]. However, in very hot countries and where the majority of women wear veils, vitamin D levels were not significantly higher and were even lower in the summer months, as these women avoided the heat and sun by staying indoors [101,105].…”
Section: Latitude and Seasonmentioning
confidence: 99%
“…Furthermore, several genetic association studies have demonstrated relationships between polymorphisms of candidate genes and decreased BMD and fracture risk [14,20,30,39,40,42 [4]. Some have shown associations between serum 25(OH)D 3 status and BMD and osteoporotic fractures [10,17], and that 25(OH)D 3 inadequacies are associated with elevated risks of osteoporosis and osteoporotic fractures [18,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed in Argentina to determine 25OHD levels (Ladizesky et al, 1987;Oliveri et al, 1990Oliveri et al, , 1991Oliveri et al, , 1993aOliveri et al, , 1993bOliveri et al, , 1994Plantalech et al, 1997;Fradinger & Zanchetta, 2001) and in Australia at similar latitude (Need et al, 1993(Need et al, , 2000, but none were designed to assess simultaneously the vitamin D status of elderly populations living in different regions of a country that covers 3700 km from north to south, between latitude 221S and 551S.…”
Section: Introductionmentioning
confidence: 99%